Influence of Emotional Exhaustion, Job Satisfaction and Organization’s Ethical Climate on Turnover Intention - Anggraeni, Abellia Septri; Wicaksana, Harits Hijrah; Ramli, Abdul Haeba; Muhmin, Andi Hidayat (International Publisher (YAPENBI), 2025)
This study aims to analyze the influence of emotional exhaustion, job satisfaction, and organizational ethical climate on turnover intention among Mie Gacoan employees in Tangerang Regency. The high level of employee desire to change jobs is a serious challenge for organizations in maintaining a productive and competitive workforce. This study uses a quantitative approach using a purposive sampling method through the distribution of questionnaires to 110 respondents and those who have worked for less than 3 years. This purpose is to test or validate the conceptual research model. The data for this study were collected through a survey method using Google Forms, an online questionnaire application. The use of the method in data analysis Structural Equation Modeling - Partial Least Square (SEM-PLS) using SmartPLS 4 to test each indicator is valid and reliable. The results of the study indicate that emotional exhaustion, job satisfaction, and organizational ethical climate have a significant effect on turnover intention. This study provides important implications for management in designing effective strategies to reduce turnover intention through the creation of an ethical work environment, increasing job satisfaction, and managing employee emotional burden.